Pengaruh Terapi Seni (Melukis) terhadap Fungsi Kognitif pada Pasien Skizofrenia - Khadija, Nadzira Salma Noer Khadija; Prasetyaningsih, Roh Hastuti (Jurnal Terapi Wicara dan Bahasa, 2025)
Background: Clinical manife$stations in schizophre$nia re$sult in psychotic symptoms such as hallucinations, de$lusions, and motivational and cognitive$ dysfunction. Cognitive$ disorde$rs in schizophre$nia such as proce$ssing spe$e$d, ve$rbal me$mory, visuospatial, atte$ntion, and proble$m solving. One$ form of the$rapy that can be$ applie$d to improve$ cognitive$ function is art the$rapy. Objectives: to de$te$rmine$ the$ e$ffe$ct of art the$rapy (painting) on cognitive$ function in schizophre$nia patie$nts at the$ Griya PMI Pe$duli Re$habilitation. Methods: pre$-e$xpe$rime$ntal de$sign in the$ form of a one$ group pre$te$st-postte$st de$sign with a sample$ size$ of 30 pe$ople$ using purposive$ sampling. The$ instrume$nt use$d in this study was Monte$ral Cognitive$ Asse$ssme$nt (MoCA-Ina). Results: Most of the$ sample$s we$re$ male$ (60.0%); the$ dominant age$ of the$ sample$ was in the$ e$arly adulthood cate$gory (40.0%); the$ e$ducation le$ve$l was dominate$d by E$le$me$ntary E$ducation (52.0%); more$ sample$s had non-pe$rmane$nt jobs (44.0%). The$ hypothe$sis te$st obtaine$d a significant value$ of 0.000 (p<0.05), statistically the$re$ was a diffe$re$nce$ in cognitive$ability be$fore$ and afte$r the$ inte$rve$ntion. Conclusion: Art the$rapy (painting) has an e$ffe$ct on the$ cognitive$ function of schizophre$nia patie$nts in the$ Griya PMI Pe$duli re$habilitation. Keywords: Art Theraphy (Painting), Cognitive Functon, Schizophrenia